2005
DOI: 10.1117/12.622890
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablated coupling structures for optical printed circuit boards

Abstract: We report on the cost effective fabrication of 45° micromirror couplers within single-mode polymer waveguides for achieving fully embedded board-level optoelectronic interconnections. Compatibility with existing board manufacturing technology is achieved by making use of polymers with high thermal stability. The sol-gel polymers behave as negative photo resist and waveguides are patterned by UV exposure. Micromirrors are fabricated using excimer laser ablation, a very flexible technology that is particularly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Alternatively, edge connectors can again be used for this purpose. To ease the coupling and to enhance the transmission characteristics micro lenses can be used that allow the focusing of the light [10,11,12]. Concepts have been shown that use 12-channel MT pins for achieving optical connections to waveguides.…”
Section: Waveguide Integration Conceptsmentioning
confidence: 98%
“…Alternatively, edge connectors can again be used for this purpose. To ease the coupling and to enhance the transmission characteristics micro lenses can be used that allow the focusing of the light [10,11,12]. Concepts have been shown that use 12-channel MT pins for achieving optical connections to waveguides.…”
Section: Waveguide Integration Conceptsmentioning
confidence: 98%
“…Energy and pulse repetition rate (PRR) are two important process parameters highlighted by Steenberge et al [7,13,14] for the fabrication of waveguides in ORMOCER. It was observed that both parameters in uence the smoothness of side walls of guides, which remains crucial for the propagation loss.…”
Section: Introductionmentioning
confidence: 99%